Perancangan User Interface Sistem Informasi Pengelolaan Data Nilai Siswa berbasis Mobile menggunakan Metode Human Centered Design (Studi Kasus SMKN 2 Banjarbaru) - Agnes Astriani; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The influence of technological developments in life can be felt in the education aspect. However, not many schools have implemented it because there are still many limitations. At SMK 2 Banjarbaru, the process of managing student value data in the process of inputting student grades and attendance is still not a system that helps. Obtained from these problems, the researcher made a design for a User Interface Information System for Student Value Data Management Mobile using the Human Centered Design, aiming to produce a design that is guided by the user, according to the needs of the context of use and specifications of user needs. In addition to focusing on display design, it also refers to usability. evaluation Usability method Heuristic Evaluation testing usability on the user interface SIAKSE (School Academic System) domain experts and usability experts found a total of 11 problems and 5 suggestions for improvement given by the evaluator.